Vigilância aos súditos do eixo na parte brasileira da tríplice fronteira (1942-1943) - Silva, Micael Alvino da (2010)
During World War II, the natives of Germany, Italy and Japan, were considered "subjects of the Axis" In the inter-American conferences and meetings in the early 1940s, discussed in the evil that could be caused by these people if they were to contribute to the war effort of the "motherland". Afler the severance of diplomatic relations and trade (January 1942), and the subsequent declaration of war on the Axis, (August 1942), in Brazil a number of actions marked the life ofthe subjects ofthe Áxis. Our goal is to understand how they were directed and carried out surveiliance and repression of the subjects of the axis on the Brazilian side of the Triple Frontier, particularly the movement called "withdrawal ofthe subjects ofthe axis of the frontier." To achieve our main objective, we consulted the normative documents, surveys and notes filed by the various Police Stations Political and Social Order of Paraná. We also interviewed people who were forced to leave their homes and belongings according to the order of "withdrawal".